Fig. 2 in Dipnoan from the Upper Triassic of East Greenland and remarks about palaeobiogeography of Ptychoceratodus ... - Pawlak, Wojciech; Tałanda, Mateusz; Sulej, Tomasz; Niedźwiedzki, Grzegorz (Zenodo, 2020)
Fig. 2. Scheme of the measured dimensions of dental plates of Triassic dipnoans. Abbreviations: B, mediolingual junction; C1, C2, C3, C4, ends of corresponding ridges; Cp, end of the last ridge; α, angle between medial and lingual margin; ð1, ð2, ð3, angles between last ridge and corresponding ridges; BCp, BC1, BC2, C1C2, C2C3, C1Cp, C2Cp, distances between corresponding points. Based on Frederickson and Cifelli (2017). ... : Published as part of Pawlak, Wojciech, Tałanda, Mateusz, Sulej, Tomasz & Niedźwiedzki, Grzegorz, 2020, Dipnoan from the Upper Triassic of East Greenland and remarks about palaeobiogeography of Ptychoceratodus, pp. 561-574 in Acta Palaeontologica Polonica 65 (3) on page 564, DOI: 10.4202/app.00679.2019, http://zenodo.org/record/12195358 ...